Metode Pelaksanaan Pekerjaan Bore Pile Jembatan Teluk Kendari - Tryagum Tryagum; Sulha Sulha; Wayan Mustika (Media Konstruksi : Jurnal Ilmiah Teknik Sipil, 2023)
AbstractThe government continues to promote infrastructure development outside Java as an effort to equalize development, including Kendari City. This study aims to determine the implementation method, requirements and standards of bore pile work in the Kendari Bay Bridge project. The results of the research on the method of carrying out bore pile work on the Kendari Bay Bridge project include a series of preparations for casing bore pile erection, mobilization of bore pile steel casing, erection of bore pile steel casing, connection of bore pile steel casing, setting of RCD tools then drill bore pile points to the desired depth. specified on the plans, rebar installation, bore pile casting. Material requirements and standards used in bore piles for concrete use high-strength SCC (Self Compacting Concrete) concrete with a quality of fc 30 Mpa, by adding Retarder RD, Super Plastic SP and Fly Ash.AbstrakPengembangan infrastruktur di luar pulau Jawa terus digenjot pemerintah sebagai upaya pemerataan pembangunan, termasuk Kota Kendari. Penelitian ini bertujuan untuk mengetahui metode pelaksanaan, syarat dan standar pekerjaan bore pile di proyek Jembatan teluk Kendari. Hasil penelitian metode pelaksanaan pekerjaan bore pile pada proyek Jembatan Teluk Kendari antara lain rangkaian persiapan pemancangan casing bore pile, mobilisasi casing baja bore pile, pemancangan casing baja bore pile, penyambungan casing baja bore pile, setting alat RCD kemudian bor titik bore pile sampai kedalaman yang telah ditentukan pada gambar rencana, instalasi rebar, pengecoran bore pile. Syarat dan standar material yang dipakai pada bore pile untuk beton menggunakan beton mutu tinggi SCC (Self Compacting Concrete)  dengan mutu fc 30 Mpa, dengan menambahkan Retarder RD, Super Plasitis SP dan Fly Ash.